A Study of Microfinance and Its Impact on the Livelihoods of Market Women; Evidence from Yilo Krobo Municipality, Ghana - Affum, Frederick (European Scientific Journal, ESJ, 2020)
The study examined the impacts of microfinance on the livelihoods of market women in the Yilo Krobo Municipality in the eastern region of Ghana. The mixed method approach was adopted thus using both qualitative and quantitative methods of collecting data. Questionnaires were distributed to market women selected conveniently whiles some purposively selected staffs and management of microfinance institutions (MFIs) were interviewed. The study revealed a positive impact of microfinance on the livelihoods of market women and their households. It was recommended that Microfinance Institutionsshould intensify the awareness of their services and maximize their training and education services for market women in the municipality to optimize the benefits derived by these market women in a way of subscribing to their services.